ETHNOBOTANIC CONTRIBUTION OF CAMEROON: ANTI-HYPERTENSIVE PLANTS INVENTORY IN THE NKOUNG –KHI DIVISION WEST REGION CAMEROON - EMMANUEL, KOYEU TATOU; GRACE, MENDI; XAVIER, TCHAMAGO FRANCOIS; VALCIN, FRANKLIN; COLLAZO, LINDA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
High blood pressure is a chronic affection closely linked to fatal complications and is spread over the whole world. However, tradi-therapists can cure them from their symptoms and complications. This study has been carried out in the Nkoung-khi Division of the Western Region of Cameroon in a bid to contribute to the ethnobotanic of Cameroon by making an inventory of the anti-hypertensive plants. Meanwhile, the main objective is to be able to treat patients suffering from the pathologies. At the end of our surveys, we have interviewed 1OO people for a total of 23 anti-hypertensive plants belonging to 15 botanic families and to 19 species. The evaluation of the results shows men are the most represented, followed by women. On the other hand, we notice that the most exploited family is that of the asteraceae, the most used part of the plant is the leaves, and decoction is the privileged preparation mode. Given that the practical interest of our investigations is to put at the disposal of the public and at low costs effective products coming from local plants, it will be desirable to reinforce the integration of these species in agro forestry projects, and the reinforcement of their protection for a better participative management so as to raise and assure the maintenance of the potential of these species.